2021
DOI: 10.1097/md.0000000000024352
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the analgesic effect of superficial or deep anterior serratus plane block on patients undergoing thoracoscopic lobectomy

Abstract: The effectiveness of anterior serratus plane block in postoperative analgesia of thoracic surgery is beginning to emerge. Currently, there are 2 methods of anterior serratus plane block: deep serratus plane block (DSPB) and superficial serratus plane block (SSPB). In clinical practice, there is no an unified view regarding the advantages and disadvantages between 2 methods. This study aimed to observe and compare the analgesic effects of 2 methods on patients undergoing thoracoscopic lobectomy, in order to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
(4 reference statements)
1
29
0
Order By: Relevance
“…In contrast, because of their origin and trajectory, the long thoracic nerve cannot be blocked by the deep serratus plane block. [16] In this study, the median time to first analgesia rescue was longer in the superficial serratus block group (P < .001), which was similar to that observed in the case series reported by Bhoi et al [19] An earlier study by Blanco's among healthy volunteers found longer duration of paresthesia with the superficial than the deep serratus plane block, where mean duration (SD) of paresthesia was 752 (21) minutes and 386 (160) minutes, respectively. [4] Abdallah however found no difference in time to first analgesic request between the blocks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, because of their origin and trajectory, the long thoracic nerve cannot be blocked by the deep serratus plane block. [16] In this study, the median time to first analgesia rescue was longer in the superficial serratus block group (P < .001), which was similar to that observed in the case series reported by Bhoi et al [19] An earlier study by Blanco's among healthy volunteers found longer duration of paresthesia with the superficial than the deep serratus plane block, where mean duration (SD) of paresthesia was 752 (21) minutes and 386 (160) minutes, respectively. [4] Abdallah however found no difference in time to first analgesic request between the blocks.…”
Section: Discussionsupporting
confidence: 86%
“…Axillary lymph node dissection or clearance involved extension of the surgical incision to the lateral aspect of the hemithorax, where the superficial serratus plane block would provide adequate analgesic coverage, but not the deep serratus plane block. [ 16 ] Their patients who did not have axillary clearance may not have benefited from the added analgesic coverage provided by the superficial serratus plane block, hence possibly accounting for the comparable results. In our study, all the patients had mastectomy and axillary clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serratus anterior plane block is a block that has been described in recent years and aims to block the thoracodorsal nerve (anesthesia in thoracic dermatomes, T2-T12) [3] . It is used in breast surgeries, rib fractures, thoracic surgeries, and traumas to provide analgesia in the postoperative period and in the placement of subcutaneous implantable cardioverter-defibrillator (S-ICD) for the intraoperative anesthesia [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been reported to provide efficient analgesia in many different trials such as; in patients with multiple rib fracture compared to TEA and PVB [11] , in breast cancer surgeries [12] and minimal invasive heart surgeries .13 Previous trials were conducted to evaluate the effect of SAPB compared to the TEA in thoracic surgeries. 14, 15,16,17 This study aimed to evaluate the effect of SSPB, DSPB and TEA in thoracotomies in patients with lung cancer. Moreover, Ökmen et al in 2018; compared DSPB to continuous TEA during the postoperative period of thoracotomy and reported that both groups were comparable regarding the VAS scores and the amounts of post-operative analgesic consumption.…”
Section: Discussionmentioning
confidence: 99%